Strengthening Social Care Character in Preventing Bullying Behavior in Elementary School Through the Role of Peers - Inah Oktarini; Ana Andriani (Proceedings Series on Social Sciences & Humanities, 2023)
This research was conducted considering the tendency of bullying behavior which has now become a phenomenon that often occurs, especially in the world of education. One way that can be done to prevent it is through the application of social caring characters with support from peers because students spend more time with their friends. This study aims to describe the processof implementing social care characters through the role of peers in preventing bullying behavior in schools. The method used is qualitative descriptive with a case study approach. The informants in this study were class teachers and learners. Data collection techniques through interviews, observation, and documentation studies. The dataanalysis technique used is the Miles and Huberman model which includes data reduction, data presentation, and conclusions. The results of the study concluded that the application of social care characters through support from peers can prevent bullying behavior in students.